Answer:
the first one x is 6 and y is 11
the second one y is 5 and x is 3
the third one x is 15 and y is 17
the fourth one y is 15 and x is -12
Explanation:
to find the first answer you have to use the actual equation given and substitute the value of x in it
y=-2(-6)/3+7
=12/3+7
=4+7
=11
the second one is quite different because the value of y has been given and not x so you have to substitute the value of y in the equation which is 5
5=-2x/3+7
5-7=-2x/3
-2/1=-2x/3
-2x/-2=-6/-2
x=3
for the third one you have to solve it like the first one
y=-2(15)/3+7
=10+7
=17
the fourth one is similar to the second one
15=-2x/3+7
15-7=2x/3
8=2x/3
-2x/-2=24/-2
x=-12
I hope this helps